Cobalt Protoporphyrin Downregulates Hyperglycemia-Induced Inflammation and Enhances Mitochondrial Respiration in Retinal Pigment Epithelial Cells - Peng-Hsiang Fang; Tzu-Yu Lin; Chiu-Chen Huang; Yung-Chang Lin; Cheng-Hung Lai; Bill Cheng (Antioxidants)
Diabetic retinopathy is characterized by hyperglycemic retinal pigment epithelial cells that secrete excessive pro-inflammatory cytokines and VEGF, leading to retinal damage and vision loss. Cobalt protoporphyrin (CoPP) is a compound that can reduce inflammatory responses by inducing high levels of HO-1. In the present study, the therapeutic effects of CoPP were examined in ARPE-19 cells under hyperglycemia. ARPE-19 cells were incubated in culture media containing either 5.5 mM (NG) or 25 mM (HG) glucose, with or without the addition of 0.1 µM CoPP. Protein expressions in samples were determined by either Western blotting or immunostaining. A Seahorse metabolic analyzer was used to assess the impact of CoPP treatment on mitochondrial respiration in ARPE-19 cells in NG or HG media. ARPE-19 cells cultured in NG media displayed different cell morphology than those cultured in HG media. CoPP treatment induced high HO-1 expressions and significantly enhanced the viability of ARPE-19 cells under hyperglycemia. Moreover, CoPP significantly downregulated expressions of inflammatory and apoptotic markers and significantly upregulated mitochondrial respiration in APRPE-19 cells under hyperglycemia. CoPP treatment significantly enhanced cell viability in ARPE-19 cells under hyperglycemia. The treatment also downregulated the expressions of pro-inflammatory and upregulated mitochondrial respiration in the hyperglycemic cells.